Synthesis and Antibacterial Activity of Metal(loid) Nanostructures by Environmental Multi-Metal(loid) Resistant Bacteria and Metal(loid)-Reducing Flavoproteins - Figueroa, Maximiliano; Fernandez, Valentina; Arenas-Salinas, Mauricio; Ahumada, Diego; Muñoz-Villagrán, Claudia; Cornejo, Fabián; Vargas, Esteban; Latorre, Mauricio; Morales, Eduardo; Vásquez, Claudio; Arenas, Felipe (Frontiers in Microbiology, 2018)
Microbes are suitable candidates to recover and decontaminate different environments from soluble metal ions, either via reduction or precipitation to generate insoluble, non-toxic derivatives. In general, microorganisms reduce toxic metal ions generating nanostructures (NS), which display great applicability in biotechnological processes. Since the molecular bases of bacterial reduction are still unknown, the search for new -environmentally safe and less expensive- methods to synthesize NS have made biological systems attractive candidates. Here, 47 microorganisms isolated from a number of environmental samples were analyzed for their tolerance or sensitivity to 19 metal(loid)s. Ten of them were highly tolerant to some of them and were assessed for their ability to reduce these toxicants in vitro. All isolates were analyzed by 16S rRNA gene sequencing, fatty acids composition, biochemical tests and electron microscopy. Results showed that they belong to the Enterobacter, Staphylococcus, Acinetobacter, and Exiguobacterium genera. Most strains displayed metal(loid)-reducing activity using either NADH or NADPH as cofactor. While Acinetobacter schindleri showed the highest tellurite (TeO32-) and tetrachloro aurate (AuCl4-) reducing activity, Staphylococcus sciuri and Exiguobacterium acetylicum exhibited selenite (SeO32-) and silver (Ag+) reducing activity, respectively. Based on these results, we used these bacteria to synthetize, in vivo and in vitro Te, Se, Au, and Ag-containing nanostructures. On the other hand, we also used purified E. cloacae glutathione reductase to synthesize in vitro Te-, Ag-, and Se-containing NS, whose morphology, size, composition, and chemical composition were evaluated. Finally, we assessed the putative anti-bacterial activity exhibited by the in vitro synthesized NS: Te-containing NS were more effective than Au-NS in inhibiting Escherichia coli and Listeria monocytogenes growth. Aerobically synthesized TeNS using MF09 crude extracts showed MICs of 45- and 66 µg/ml for E. coli and L. monocytogenes, respectively. Similar MIC values (40 and 82 µg/ml, respectively) were observed for TeNS generated using crude extracts from gorA-overexpressing E. coli. In turn, AuNS MICs for E. coli and L. monocytogenes were 64- and 68 µg/ml, respectively.